Language Crimes in the Form of Threats at the Gorontalo Regional Police and Their Implications for Indonesian Language Learning in High Schools - Elastri Bahutala; Supriyadi; Asna Ntelu (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the forms of language crimes (word groups and clauses) of threats in the Gorontalo Regional Police; describe the function of language crimes in the form of threats in the Gorontalo Regional Police; describe the meaning of language crimes in the form of threats in the Gorontalo Regional Police; and how the results of this study are implied in Indonesian language learning in high schools. This study uses a qualitative descriptive method of case study type with a forensic linguistic approach. The research data sources are official documents in the form of data recaps of language crime cases containing threats from the Gorontalo Regional Police and its relatives (Gorontalo City Police, Bone Bolango Police, and Gorontalo Resort Police) during a certain period. The data were analyzed systematically through the stages of data reduction, data presentation, and drawing conclusions, using pragmatic theory to analyze function and meaning. The results of the study show that from 11 cases of language crimes in the form of threats in the Gorontalo Regional Police, namely 7 word groups, namely "viral," "kill," "hit," "die," "bage," and "cut-piece". There were eight clauses, predominantly declarative or declarative, and conditional. The linguistic functions of threats were identified as conative and emotive, each representing 11 items. The meaning of the threats was analyzed based on their conceptual and contextual meanings. The conceptual meanings of the word groups identified directly refer to violence and harm. The contextual meanings emphasized the intent of the threats, considering the addressee and their primary purpose, which was to intimidate and frighten the victim. The results of this study can be used as case studies to train students not only to be linguistically skilled but also to be ethically, critically, and socially and legally responsible.